Monoaminergic Antidepressants in the Relief of Pain: Potential Therapeutic Utility of Triple Reuptake Inhibitors (TRIs) - Bruno P. Guiard; Alain M. Gardier; Guillaume Hache; François Coudore (MDPI AG, 2011)
Over 75% of depressed patients suffer from painful symptoms predicting a greater severity and a less favorable outcome of depression. Imaging, anatomical and functional studies have demonstrated the existence of common brain structures, neuronal pathways and neurotransmitters in depression and pain. In particular, the ascending serotonergic and noradrenergic pathways originating from the raphe nuclei and the locus coeruleus; respectively, send projections to the limbic system. Such pathways control many of the psychological functions that are disturbed in depression and in the perception of pain. On the other hand, the descending pathways, from monoaminergic nuclei to the spinal cord, are specifically implicated in the inhibition of nociception providing rationale for the use of serotonin (5-HT) and/or norepinephrine (NE) reuptake inhibitors (SSRIs, NRIs, SNRIs), in the relief of pain. Compelling evidence suggests that dopamine (DA) is also involved in the pathophysiology and treatment of depression. Indeed, recent insights have demonstrated a central role for DA in analgesia through an action at both the spinal and suprasinal levels including brain regions such as the periaqueductal grey (PAG), the thalamus, the basal ganglia and the limbic system. In this context, dopaminergic antidepressants (i.e., containing dopaminergic activity), such as bupropion, nomifensine and more recently triple reuptake inhibitors (TRIs), might represent new promising therapeutic tools in the treatment of painful symptoms with depression. Nevertheless, whether the addition of the dopaminergic component produces more robust effects than single- or dual-acting agents, has yet to be demonstrated. This article reviews the main pathways regulating pain transmission in relation with the monoaminergic systems. It then focuses on the current knowledge regarding the in vivo pharmacological properties and mechanism of action of monoaminergic antidepressants including SSRIs, NRIs, SNRIs and TRIs. Finally, a synthesis of the preclinical studies supporting the efficacy of these antidepressants in analgesia is also addressed in order to highlight the relative contribution of 5-HT, NE and DA to nociception.